The extent and structure of peri-urban smallholder dairy farming in five cities in India - Lindahl, Johanna F.; Chauhan, A.; Gill, J.P.S.; Hazarika, R.A.; Fairoze, N.M.; Grace, Delia; Gaurav, A.; Satpathy, S.K.; Kakkar, M. (Frontiers Media, 2020)
Livestock keeping is common in many cities in India, driven by the demand for animal-source foods, particularly perishable milk. We selected five cities from different regions of the country and conducted a census in 34 randomly selected peri-urban villages to identify and describe all smallholder dairy farms. In total 1,690 smallholder dairy farms were identified, keeping on average 2.2 milking cows and 0.7 milking buffaloes. In Bhubaneswar, the proportion of cows milking was only 50%, but in other cities it was 63–73%. In two of the five cities, more than 90% of the farmers stated that dairy production was their main source of income, while <50% in the other cities reported this. In one of the cities, only 36% of the households kept milk for themselves. Market channels varied considerably; in one city about 90% of farms sold milk to traders, in another, 90% sold to the dairy cooperative, and in another around 90% sold directly to consumers. In conclusion, peri-urban dairy systems in India are important but also varying between different cities, with only one city, Bengaluru, having a well-developed cooperative system, and the northeastern poorer region being more dependent on traders. Further studies may be needed to elucidate the importance and to design appropriate developmental interventions.